2012 27th Annual IEEE Symposium on Logic in Computer Science 2012
DOI: 10.1109/lics.2012.57
|View full text |Cite
|
Sign up to set email alerts
|

An Infinitary Affine Lambda-Calculus Isomorphic to the Full Lambda-Calculus

Abstract: It is well known that the real numbers arise from the metric completion of the rational numbers, with the metric induced by the usual absolute value. We seek a computational version of this phenomenon, with the idea that the role of the rationals should be played by the affine lambda-calculus, whose dynamics is finitary; the full lambda-calculus should then appear as a suitable metric completion of the affine lambda-calculus. This paper proposes a technical realization of this idea: an affine lambda-calculus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Another closely related work is a recent one by Mazza [24], that shows how the ordinary, finitary, λ-calculus can be seen as the metric completion of a much weaker system, namely the affine λ-calculus. Again, the main commonalities with this paper are on the one hand the presence of infinite terms, and on the other a common technical background, namely that of linear logic.…”
Section: Expressive Powermentioning
confidence: 99%
“…Another closely related work is a recent one by Mazza [24], that shows how the ordinary, finitary, λ-calculus can be seen as the metric completion of a much weaker system, namely the affine λ-calculus. Again, the main commonalities with this paper are on the one hand the presence of infinite terms, and on the other a common technical background, namely that of linear logic.…”
Section: Expressive Powermentioning
confidence: 99%
“…The reduction is confluent, as the rules never duplicate any subterm. The results of [10] are formulated in an infinitary calculus with exponential variables only, whose terms and reduction are defined as follows:…”
Section: The Infinitary Affine Lambda-calculusmentioning
confidence: 99%
“…In [10], it was shown that usual λ-terms may be recovered as uniform infinitary affine terms. The categorical version of this result is that, in certain conditions, a model of the infinitary affine λ-calculus is also a model of linear logic.…”
Section: From Infinitary Affine Terms To Linear Logicmentioning
confidence: 99%
See 2 more Smart Citations